City license to Ah Luis, July 1892 - City of San Luis Obispo::::::::: (1892)
A license for Ah Louis' (spelled Luis and Louis in the document) store to operate for three months. The text of license reads: 'Ah Luis, having paid into the City Treasury one dollar, License is hereby granted to transact business of [indecipherable] in the City of San Luis Obispo, Cal., for the period of THREE MONTHS, ending Sep. 30 A.D. 18__, in conformity with the provisions of the Ordinances of said City.' Signed by the City Clerk and the City Tax Collector.